Snakes of the world : a supplement - Boundy, Jeff; Wallach, Van. (Boca Raton, FL : CRC Press, 2021)
Snakes of the World: A Catalogue of Living and Extinct Species, published in 2014, was the first catalogue of its kind and covered all living and fossil snakes described between 1758 and 2012. This new volume will be a supplement to this important herpetological reference and will include new published data on snakes named and recognized since 2012. Key Features Supplements and updates Wallach et al. - Snakes of the World - the only work to cover all living snakes in the world. Includes updates for fossil snakes named since the publication of Wallach et al. Summarizes the systematic snake literature published since the appearance of Wallach et al. Genera and species are listed alphabetically for ease of reference. Related Titles Wallach, V., K. L. Williams, and J. Boundy. Snakes of the World: A Catalogue of Living and Extinct Species (ISBN 978-1-138-03400-6) Aldridge, R. D. and D. M. Sever, eds. Reproductive Biology and Phylogeny of Snakes (ISBN 978-1-57808-701-3) Caldwell, M. W. The Origin of Snakes: Morphology and the Fossil Record (ISBN 978-1-4822-5134-0)
Supplement to: Snakes of the world : a catalogue of living and extinct species / Van Wallach, Kenneth L. Williams, Jeff Boundy, 2014.
OCLC-licensed vendor bibliographic record.
Keywords: Snakes; Extinct reptiles; NATURE / Animals; SCIENCE / Life Sciences / Evolution; SCIENCE / Life Sciences / General